Pendampingan Penyusunan Laporan Keuangan Pada Mini Market Syahada Mart - Khairiyahtussolihah, Assa'adatul; Arif, Muhammad; Sihono, Agus (Jaanur ElBarik Indonesia, 2025)
This community service program aims to enhance the ability of Syahada Mart’s management to prepare financial statements that are accurate, systematic, and in accordance with accounting principles to support business decision-making. The program was initiated based on the initial finding that the financial recording at Syahada Mart was limited to cash inflows and outflows without the preparation of an income statement, balance sheet, or cash flow statement. The methods applied included interviews, observations, documentation, hands-on practice, and training on financial statement preparation using a Microsoft Excel-based template. Through the mentoring activities carried out in collaboration with Accounting Study Program students, this program successfully produced financial statements that can be utilized by management as a basis for evaluating and controlling financial performance